THE COST OF INDIFFERENCE IN A MEDICAL NEGLIGENCE CASE: Lushaba v MEC for Health, Gauteng (17077/2012 [2014] ZAGPJHC 407 (16 October 2014)) - Freddy Mnyongani; Magda Slabbert (Obiter, 2018)
The much-debated diagnostic report, the National Development Plan 2030 (NDP), paints a worrying picture about the state of the health system in South Africa. The NDP simply states that, “At institutional level, healthcare management is in crisis” (Republic of South Africa 2012, National Development Plan of 2030: 52). One of the remedial measures proposed by the NDP is the introduction of the National Health Insurance in South Africa (Republic of South Africa 2012, National Development Plan of 2030: 52). It is hoped that the National Health Insurance “will ensure that everyone has access to appropriate, efficient and quality health services” (Republic of South Africa 2012, National Development Plan of 2030: 4). The Constitution of the Republic of South Africa, 1996 sets the benchmark and the ideals towards which public servants must strive as they deliver the much-needed services to the general populace (s 195(1)(a)−(i)). Among others, public servants must promote and maintain a high standard of professional ethics (s 195(1)(a)). Further, the Batho Pele Principles require it of government institutions to, inter alia communicate the level and quality of service, which the public must expect from them (Batho Pele Principles Principle 2). It is therefore not misguided to say that generally, people are aware of the standard of service they should expect from state institutions. As a matter of fact, people have gone to the courts of law to hold state institutions accountable. In this regard the medical fraternity has in the recent past witnessed an upsurge of court cases of negligence against the health department. This rise in litigation has led to a crisis of another kind. According to the Minister of Health, healthcare in South Africa is facing a crisis because some medical practitioners, particularly gynaecologists and obstetricians, have opted not to perform operations for fear of lawsuits. The concerns of the Minister notwithstanding, the daily experiences of people point to the fact that despite the lofty ideals in the Constitution and the Batho Pele Principles, the general public continues to receive sub-standard service from public institutions, especially from public hospitals. The case of Lushaba v MEC for Health, Gauteng (The original case) provides a good illustration of a nation, which is in a state of paralysis ethically. The case paints a picture of “state employees who could not be bothered to do their work” (The rule nisi case par 87). What is even more ominous is the observation by Robinson JA that shaming such public officials no longer has any effect (The rule nisi case par 90). The Lushaba case has all the hallmarks of the cost of indifference on the ethical values of a nation. Axiomatically, such a cost cannot only be measured in Rands and cents. Later in the discussion, we hope to make it clear that indifference impacts on the valuable time of the court and the plaintiff, the reputation of the various institutions involved, quality of life of the child born with cerebral palsy as a result of indifference, the dignity of both the mother and her son and, of course, the taxpayers’ money. These factors combined provide a good basis for reflection on the cost of indifference in this case. To provide some background, the facts of the Lushaba case are discussed briefly, after which the indifference of every role player in the events leading up to the two court cases are highlighted. In the process, our discussion also makes mention of the trajectory that the case followed from the court a quo all the way to the Constitutional Court (MEC for Health, Gauteng v Lushaba [2015] ZACC 16). In the Constitutional Court’s judgment, even the High Court judge came under scrutiny.